Fostering Gratitude and Character Through Role Playing in Moral Education - Sholehah, Nur Rahmadhani; Arifi, Ahmad; Nurhidayat, Nurhidayat (Academia Open, 2025)
General Background: Character education has become a pivotal concern in modern pedagogy, particularly in religious and moral subjects. Specific Background: One approach gaining attention is the role playing model, which engages students actively in moral reasoning and character development. Knowledge Gap: However, empirical studies that analyze its application specifically within the context of gratitude in Islamic character education remain limited. Aims: This study aims to analyze the implementation of the role playing model in shaping character education related to gratitude in Akidah Akhlak learning at UIN Sunan Kalijaga. Results: Using a qualitative phenomenological approach with observation, interviews, and documentation, findings indicate that role playing facilitates the internalization of feelings, values, and perspectives. The structured process—beginning with prayer and material explanation, followed by group division, script discussions, dramatization, and meaning reflection—promotes character traits such as gratitude, sincerity, patience, care, and responsibility. Novelty: This study highlights how direct student engagement through dramatization uniquely fosters affective and behavioral dimensions of character. Implications: Despite some challenges (e.g., student shyness, classroom dynamics), the method demonstrates strong potential in cultivating religious values, suggesting broader applicability in moral education contexts. Highlights: Promotes internalization of religious values through active participation. Enhances moral traits like gratitude, sincerity, and responsibility. Uses dramatization to foster empathy and character understanding. Keywords: Role Playing, Character Education, Gratitude, Akidah Akhlak, Islamic Learning